Effect of Handwriting on Visual Word Recognition in Chinese Bilingual Children and Adults - Guan, Connie Qun; Smolen, Elaine R.; Meng, Wanjin; Booth, James R. (Frontiers in Psychology, 2021)
In a digital era that neglects handwriting, the current study is significant because it examines the mechanisms underlying this process. We recruited 9- to 10-year-old Chinese children (n = 24), who were at an important period of handwriting development, and adult college students (n = 24), for both behavioral and electroencephalogram (EEG) experiments. We designed four learning conditions: handwriting-Chinese (HC), viewing-Chinese (VC), drawing shapes followed by Chinese recognition (DC), and drawing shapes followed by English recognition (DE). Both behavioral and EEG results showed that handwriting Chinese facilitated visual word recognition compared to viewing Chinese, and behavioral results showed that handwriting Chinese facilitated visual word recognition compared to drawing shapes. Handwriting and viewing Chinese resulted in a lateralization of the N170 in adults, but not in children. Taken together, the results of the study suggest benefits of handwriting on the neural processing and behavioral performance in response to Chinese characters. The study results argue for maintaining handwriting practices to promote the perception of visual word forms in the digital age.